Smart-Valleys: a locally led adaptation solution that enhanced rice yield and nutrient uptake in inland valleys of Benin, West Africa - Akodekou, A.D.; Dossou-Yovo, E.R. (2025)
Rice production in sub-Saharan Africa remains below potential due to limited water control, inefficient nutrient management, and climate variability. In Benin, inland valleys offer high potential for climate resilient rice intensification, yet productivity is constrained by unmanaged hydrological regimes and low nutrient-use efficiency. This study evaluated the locally led Smart-Valleys approach, which engages farmers in co-designing, constructing, and collectively managing low-cost water control structures adapted to local topography and rainfall patterns. Multi-location, multi-season field trials across two contrasting agro-ecological zones, co-designed and co-managed with farmers, assessed the effects of Smart-Valleys combined with three fertilization regimes and three rice varieties on hydrological status, grain yield, and nutrient efficiency. Results show that Smart-Valleys significantly improved the hydrological regime, increasing water table levels, soil moisture by 9%, and reducing the Soil Dryness Index by 1.56-fold compared with undeveloped valleys, thereby buffering intra-seasonal dry spells and creating favorable root-zone conditions. Agronomic performance was enhanced, with grain yield increasing by 43% and nitrogen uptake by 36%, particularly under site-specific fertilization, demonstrating improved input use efficiency. These findings highlight that Smart-Valleys represents a scalable, locally led adaptation that strengthens water and soil system resilience, mitigates drought risk, and enhances rice productivity and nutrient efficiency in inland valley ecosystems.